2020
DOI: 10.3389/fpsyg.2020.00365
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Early Screening and Prompt Intervention to Identify and Treat Maternal Perinatal Mental Health. Protocol for a Prospective Multicenter Study in Italy

Abstract: Background: The most common mental disorders in women during the perinatal (antenatal and postnatal) period are depressive syndromes and anxiety syndromes. The global prevalence of maternal perinatal depression ranges from 10 to 20%, while the prevalence of perinatal anxiety ranges from 10 to 24%. The comorbidity of mood and anxiety disorders in perinatal women is common, reaching 40%. In Italy, a few studies have been undertaken to evaluate the prevalence of perinatal depression and anxiety, and there is stil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 80 publications
(81 reference statements)
0
17
0
Order By: Relevance
“…This study was conducted as part of a multicentre, longitudinal study called the “Screening and early intervention for perinatal anxiety and depressive disorders: Prevention and promotion of mothers', children's, and fathers' mental health.” The study design was developed in mutual agreement of scientific collaboration between the University of Brescia, Department of Clinical and Experimental Sciences, Section of Neuroscience, Observatory of Perinatal Clinical Psychology ( https://www.unibs.it/it/node/988 ) and the Italian National Institute of Health. Information about the rationale and methodology of the whole study were detailed in the study protocol ( 26 ). Ethical approval was granted by the Ethical Committee of the Healthcare Centre of Bologna Hospital (Register Number: 0077805, June 27, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…This study was conducted as part of a multicentre, longitudinal study called the “Screening and early intervention for perinatal anxiety and depressive disorders: Prevention and promotion of mothers', children's, and fathers' mental health.” The study design was developed in mutual agreement of scientific collaboration between the University of Brescia, Department of Clinical and Experimental Sciences, Section of Neuroscience, Observatory of Perinatal Clinical Psychology ( https://www.unibs.it/it/node/988 ) and the Italian National Institute of Health. Information about the rationale and methodology of the whole study were detailed in the study protocol ( 26 ). Ethical approval was granted by the Ethical Committee of the Healthcare Centre of Bologna Hospital (Register Number: 0077805, June 27, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…The study was conducted as part of the "Screening e intervento precoce nelle sindromi d'ansia e di depressione perinatale. Prevenzione e promozione salute mentale della madre-bambino-padre" (Screening and early intervention for perinatal anxiety and depressive disorders: Prevention and promotion of mothers', children's, and fathers' mental health) project [26] coordinated by the University of Brescia's Observatory of Perinatal Clinical Psychology and the Italian National Institute of Health (Istituto Superiore di Sanità, ISS). The main objectives of this Italian multicenter project were to apply a perinatal depression and anxiety screening procedure that could be developed in different structures, as it requires the collaboration and connection between structurally and functionally existing resources, and to evaluate the effectiveness of the psychological intervention of Milgrom and colleagues [27][28][29] for both antenatal and postnatal depression and/or anxiety in Italian setting.…”
Section: Outline Of the Studymentioning
confidence: 99%
“…All these aspects must be considered when working during disasters such as the ongoing pandemic because, as highlighted by a systematic review on the effects of disaster on pregnancy and the postpartum period, they have an indirect impact on maternal mental health and some perinatal health outcomes (33). Moreover, it has been observed that the welldocumented negative influence of mother's mental health on child development (34,35) may be even greater after a disaster than any direct effect of disaster-related prenatal stress (33).…”
Section: Discussionmentioning
confidence: 99%